The acquisition of morphosyntactic agreement in the interlanguage system of AFL learners in Ghana - Husein, Alhassan Abdur-Rahim (AUC Knowledge Fountain, 2013)
Despite the relevance of agreement structures in constructing the interlanguage (IL) system of the L2 learner, not much research has been conducted in this area on Arabic language learners. This study investigated the acquisition of morphosyntactic agreement structures by Arabic as Foreign Language (AFL) learners in Ghana, using the Processability Theory (PT) formulated in Pienemann (1998, 2005). The theory predicts cross-linguistic developmental routes for the acquisition of grammatical structures. A cross-sectional study was performed in order to test the theory. Data were elicited from 15 participants from the University of Ghana, Legon using Grammaticality Judgment Task and Elicited Production Task. Five Arabic morphosyntactic agreement structures at the phrasal, inter-phrasal and subordinate clause processing procedure stages of Pienemann' s implicational hierarchy were tested. The data collected were analysed by using distributional analysis, a pre-defined emergence criterion and implicational scaling. The results of the study suggest that: (1) acquisition of agreement structures by AFL learners in Ghana seems to develop, generaly, according to PT's predictions; (2) there is enough evidence for the stability of developmental stages. In effect, that seems to confirm the cross-linguistic plausibility of the theory and (3) no significant differences were found in the acquisition of the Noun Predicative Adjective (an inter-phrasal structure) among all the participants. These findings were discussed in the light of L1 transfer and variation and processing constraints. The study highlights the importance of teaching L2 learners structures that they are cognitively and developmentally ready to process so that the entire teaching practice would be beneficial. Otherwise, learners IL development becomes stagnated, teaching becomes ineffective and precious classroom time is wasted, eventually.